Human‐Machine Interfaces: A Delta‐Parallel‐Inspired Human Machine Interface by Using Self‐Powered Triboelectric Nanogenerator Toward 3D and VR/AR Manipulations (Adv. Mater. Technol. 1/2021). Issue 1 (5th January 2021) - Hou, Cheng; Geng, Jiangjun; Yang, Zhan; Tang, Tianyi; Sun, Yuyang; Wang, Fengxia; Liu, Huicong; Chen, Tao; Sun, Lining
Abstract : A delta‐parallel‐inspired human machine interface (DT‐HMI) towards 3D and VR/AR manipulation is proposed by Huicong Liu, Tao Chen, Lining Sun, and co‐workers (article number 2000912 ). By using three pairs of self‐powered sensing gears based on triboelectric effect, the three pairs of sensing gears with six electrodes define the 512 virtual‐sensing pixels. The low‐cost, simple‐designed DT‐HMI controller can achieve remote control and spatial position mapping.